Genomic analysis and replication kinetics of the closely related EHV-1 neuropathogenic 21P40 and abortigenic 97P70 strains - Eslam Mohamed; Ines Zarak; Nick Vereecke; Sebastiaan Theuns; Kathlyn Laval; Hans Nauwynck (Veterinary Research)
Abstract Varicellovirus equidalpha 1, formerly known as Equid alphaherpesvirus 1 (EHV-1), is highly prevalent and can lead to various problems, such as respiratory problems, abortion, neonatal foal death, and neurological disorders. The latter is known as equine herpes myeloencephalopathy (EHM). Cases of EHM have significantly increased since the beginning of the twenty-first century. The genomic sequences of five isolates associated with the fatal neurological outbreak in Valencia, Spain, in 2021 were analyzed and documented. The genome and replication kinetics of the Belgian EHM isolate 21P40, associated with the Valencia outbreak, and the well-characterized abortigenic strain 97P70 were compared. Both strains exhibited a nucleotide identity of 99.96%, with only seven genetic mutations in ORFs 13, 24, 30, 32, 40, 65, and 71. Isoleucine and asparagine at loci 291 and 207 of ORF30 (DNA polymerase) and ORF65 (ICP22), respectively, were unique to isolates from the Valencia outbreak. The replication kinetics of these two genetically closely related strains were determined in rabbit kidney (RK-13), equine respiratory, and vaginal mucosal explant cells, as well as equine blood monocytes (CD172a+). Both strains replicated equally well in RK-13 cells. The neuropathogenic isolate 21P40 exhibited a more extensive infection in respiratory explants and blood monocytes, as demonstrated by more plaques and single infected leukocytes, and a higher percentage of infected monocytes. In contrast, vaginal explants infected with the abortigenic strain 97P70 demonstrated more plaques and single infected leukocytes. In conclusion, 21P40 replicated significantly different compared to 97P70 but shared similarities with the Belgian well-studied neuropathogenic EHV-1 strain 03P37.